Clustering of business strategies among Indonesian manufacturing firms - Esti Dwi Rinawiyanti; Argo Hadi Kusumo (International Journal of Communication and Society, 2023)
This study aims to to classify business strategies adopted by manufacturing firms. Data were acquired by sending questionnaires to Indonesian manufacturing firms in Java. Factor and cluster analysis were performed on 435 survey data. Using principal component analysis and varimax rotation, the factor analysis identified two distinct business strategies based on Porter's generic strategy: cost leadership and differentiation. Hierarchical and K-means clustering conducted sequentially enabled the identification of three clusters of business strategy: cost leadership, differentiation, and no strategy. According to the findings, the majority of Indonesian manufacturing firms utilize the differentiation strategy, followed by the cost leadership strategy. Only a small percentage of firms employ no strategy at all. The descriptive analysis of each cluster shows that the number of firms adopting the differentiation strategy is significantly higher than those pursuing the cost leadership strategy in a number of products, including food and beverage, computers, electronic, and optical products, as well as machinery and electrical equipment. For some products, such as automotive and furniture, the percentage of firms using cost leadership or differentiation strategies is comparable. Large firms dominate both clusters. Nevertheless, there are more large firms in the differentiation cluster than in the cost leadership cluster. The findings of this study enrich the body of knowledge in the domains of strategic management and manufacturing by classifying the business strategies that help firms achieve their business objectives, particularly in the context of emerging countries.